Career Conversations in Small- to Medium-Sized Businesses: A Competitive Advantage - Borgen, William A.; Butterfield, Lee D.; LaLande, Vivian (Canadian Journal of Counselling and Psychotherapy, 2012)
Career conversations are career-related dialogues between managers and employees that are intended to facilitate the development of specific goals and a plan for employee development that is mutually beneficial—to align the career goals of the employee with the organization’s goals. The aim of these conversations is to address the turnover, engagement, and absenteeism issues employers currently face. This article focuses on a pilot study that designed, delivered, and assessed career conversation resources for managers and employees from small-and medium-sized enterprises. The results provide some evidence that career conversations are potentially beneficial to managers and employees. The mixed-methods design,results, and impacts of the intervention for both managers and employees, and implications for organizations and counselling are also discussed.